The impact of site-specific soil fertility recommendations: Experimental evidence from Malawi - Van Campenhout, Bjorn; De Weerdt, Joachim; Assefa, Thomas; Spielman, David J.; Siyame, Edwin W. P.; Ariong, Richard M.; Atkinson, Jonathan (AEA RCT Registry, 2024)
Raising agricultural productivity among smallholder farmers in Sub-Saharan Africa is widely recognized as an important component of inclusive wealth creation and structural transformation. Central to this endeavor will be the adoption of sustainable soil and land management to improve the sustainability, resilience and productivity of agriculture. As such, government advise farmers to increase soil productivity by embracing the use of fertilizers and implement proper soil health management practices. However, these recommendations mostly come in the form of blanket one-size-fits-all recommendations that ignore heterogeneity in soil characteristics that individual farmers face. Using a cluster randomize control trial, we evaluate the impact of a bundled intervention that involves offering farmers a soil test on a plot they select and, using the results of this soil test, provide them with tailored advise on soil management to attain a desired yield for a particular crop the farmer chooses to plant on the plot. Furthermore, we also explore resources constraints as a potential barrier to the adoption of site specific fertilizer blends by adding a subsidy.